Preparation method of spherical TiO2-coated inorganic particle composite material and light reflection coating of spherical TiO2-coated inorganic particle composite material

By preparing spherical TiO2-coated inorganic particle composite materials, and using fluidized bed technology to spray TiO2 balls onto the surface of the inorganic particle core material, the problem of insufficient light reflection performance in the prior art is solved, and high-efficiency light reflection and material stability are achieved in the 400-2500nm band.

CN119799052AActive Publication Date: 2025-04-11ZHENGZHOU UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510029346.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-11
Estimated Expiration
2045-01-08

AI Technical Summary

Technical Problem

The light reflection performance of the prior art in the 400-2500nm band is insufficient, making it difficult to meet the current application needs.

Method used

The preparation method of spherical TiO2 coated inorganic particle composite material is adopted to prepare rutile-type TiO2 spheres through hydrothermal reaction, and the TiO2 spheres are sprayed onto the surface of the inorganic particle core material by fluidized bed technology to form a spherical TiO2 coated inorganic particle composite material.

Benefits of technology

The light reflection performance of the composite material in the 400-2500nm band is significantly improved, the reflection directionality and reflectivity of the light are enhanced, and the stability and corrosion resistance of the material are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119799052A_ABST
    Figure CN119799052A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a spherical TiO2 coated inorganic particle composite material and a light reflection coating thereof, and belongs to the technical field of composite coatings. The invention relates to a preparation method of a spherical TiO2 coated inorganic particle composite material. The preparation method comprises the following steps: preparing rutile type TiO2 spheres; opening a feed valve of the fluidized bed, and introducing the inorganic particle core material into a stock bin of the fluidized bed; closing a feeding valve, adjusting the height of the fluidized bed, starting a bottom gas pump, and adjusting to a set gas flow speed, so that bed layer particles enter a fluidized state; adding the spherical TiO2 into ethanol to obtain a TiO2 ethanol solution, regulating the viscosity, introducing the TiO2 ethanol solution into a liquid flowing bin, setting spraying pressure and spraying rate, spraying the TiO2 ethanol solution to the surface of the inorganic particle core material, keeping proper air inlet temperature and air outlet temperature, stopping spraying the TiO2 ethanol solution after a preset thickness is reached, and continuously keeping the air flow to completely dry the particles, so as to obtain the inorganic particle core material. The spherical TiO2 coated inorganic particle composite material is obtained. The preparation method is used for improving the light reflection performance of the composite material in the wave band of 400-2500nm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of composite materials, and particularly relates to a spherical TiO 2 A preparation method of a composite material coated with inorganic particles and a light-reflecting coating thereof. Background Art

[0002] TiO 2 Due to its small particle size, large specific surface area, and large proportion of interface atoms, it has very unique properties, such as excellent UV shielding, transparent and non-toxic, unique color effects, and photocatalytic effects. 2 It has broad application prospects in the automotive industry, sunscreen cosmetics, advanced coatings, wastewater treatment and sterilization, environmental protection, adsorbents and functional ceramic materials. 2 There are many preparation methods, which are mainly divided into gas phase method and liquid phase method. Different preparation methods have different process control conditions and different product properties.

[0003] In the prior art, TiO 2 It is often used alone as one of the components of exterior wall reflective coatings, such as CN1749331A, a solar thermal exterior wall reflective coating, CN110684411A, a TiO 2 Reflective heat-insulating topcoat and its preparation and application, CN103834216A an exterior wall heat-insulating reflective paint additive, etc.

[0004] With the development of science and technology and the diversification of needs, some properties of coatings prepared from traditional single materials can no longer meet the current application requirements. 2 It is compounded with other reflective components through a specific process. For example, CN114316695A is to combine glass powder and TiO 2 Prepare microspheres with a reflective shell, the preparation steps comprising: S11, mixing glass powder and TiO 2 , stirring evenly under the conditions of a water bath temperature of 20-30°C and a rotation speed of 2000r / min-3000r / min to obtain a modified functional filler; S12, mixing a dispersing stabilizer, an emulsifier, and water evenly to obtain a suspension polymerization liquid; S13, mixing and emulsifying the obtained filler and liquid to form a suspension solution, stirring the reaction in a high-pressure reactor to achieve suspension polymerization, filtering and drying to obtain highly reflective microspheres. For another example, CN116162387A is a method in which TiO is coated on the surface of glass microspheres in sequence. 2 Layer and SiO 2 The layer is prepared by the following method: titanium tetrachloride is added to a glass microbead suspension, the pH is adjusted to 3-5, and then stirred to react to obtain a surface-coated TiO 2Then, alkali metal silicate is added to the surface of the TiO 2 The pH of the glass microbead suspension was adjusted to 6-8 and stirred to obtain TiO 2 Layer coated with SiO 2 The above technologies are respectively based on TiO 2 The light reflection performance of the coating is improved to a certain extent by compounding and preparing with different light reflection materials. Summary of the invention

[0005] In view of this, the technical problem to be solved by the present invention is to provide a spherical TiO 2 A method for preparing a composite material of coated inorganic particles to improve the light reflection performance of the composite material in the 400-2500nm band.

[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is: A spherical TiO 2 The method for preparing the coated inorganic particle composite material comprises the following steps: S01: Preparation of rutile TiO 2 Ball: Add titanium tetraisopropoxide to anhydrous ethanol and glacial acetic acid and stir, and carry out hydrothermal reaction in a reactor. After the reaction is completed, centrifuge the precipitate, wash it twice with distilled water and anhydrous ethanol respectively, and dry and calcine it after the ultrasonic treatment to obtain rutile TiO 2 ball; S02: Preparation of spherical TiO 2 Coating the inorganic particle composite material: open the feed valve of the fluidized bed, and pass the inorganic particle core material into the silo of the fluidized bed; close the feed valve, adjust the height of the fluidized bed, start the bottom gas pump, and adjust the air flow speed to the set value, so that the bed particles enter the fluidized state; 2 The ball was added to ethanol to obtain TiO 2 The ethanol solution is passed into the liquid flow chamber after adjusting the viscosity, and the spray pressure and spray rate are set to spray TiO 2 Ethanol solution is sprayed onto the surface of the inorganic particle core material, maintaining appropriate inlet and outlet temperatures. After reaching the predetermined thickness, stop spraying TiO 2 Ethanol solution, continue to maintain the air flow to completely dry the particles to obtain spherical TiO 2 Coated inorganic particle composite materials.

[0007] Optionally, in step S01, the weight of titanium tetraisopropoxide is 0.165-0.495 g, the volume of anhydrous ethanol is 50-100 mL, and the volume of glacial acetic acid is 5-10 mL.

[0008] Optionally, the temperature of the hydrothermal reaction in step S01 is 150° C.-200° C., and the reaction time is 2-4 hours.

[0009] Optionally, in step S01, the drying temperature is 60-80° C. and the time is 12-24 hours, and the calcination temperature is 900-950° C. and the time is 2-4 hours.

[0010] Optionally, in step S02, the inorganic particle core material is at least one of silicon dioxide, aluminum oxide, and spinel, and has a particle size of 100-700 nm.

[0011] Optionally, in step S02, the height of the fluidized bed is 20-60 cm, the bed pressure is 4.5-5.5 MPa, and the air flow velocity is 0.1-0.5 m / s.

[0012] Optionally, in step S02, TiO 2 TiO in ethanol solution 2 The mass concentration of the ball is 60%, and the following raw materials are used to prepare TiO 2 The viscosity of the ethanol solution is regulated by at least one of polyacrylate, polyacrylic amine and polyvinyl alcohol.

[0013] Optionally, in step S02, TiO 2 The viscosity of the ethanol solution is adjusted to 800-1000 mPa·s, the spray pressure is 0.2-0.5 Mpa, the spray rate is 10-100 L / h; the inlet temperature is 30-80°C, the outlet temperature is 80-120°C; the spraying time is controlled at 30-40 min.

[0014] In a second aspect, the present invention provides a spherical TiO 2 Spherical TiO obtained by the preparation method of coated inorganic particle composite material 2 Coated inorganic particle composite materials.

[0015] In a third aspect, the present invention also provides the spherical TiO 2 Application of coated inorganic particle composites in light reflective coatings.

[0016] Optionally, the light reflective coating, the preparation method thereof comprises the following steps: providing an oligomer emulsion, a thickener, a crosslinking agent, a dispersant, a defoaming agent, tetraethyl orthosilicate, glacial acetic acid, anhydrous ethanol and water; taking the spherical TiO 2 The coated inorganic particle composite material is mixed with water, a dispersant and a defoamer to obtain component A; water, anhydrous ethanol, glacial acetic acid and tetraethyl orthosilicate are mixed and reacted to obtain component B; an oligomer emulsion, a thickener and a cross-linking agent are mixed and reacted to obtain component C; component A, component B and component C are mixed in a volume ratio of 6:3:1, and the viscosity and pH value are adjusted to obtain a coating.

[0017] Optionally, the ratio of the raw materials in the component A is as follows: spherical TiO 2 10-20g of coated inorganic particle composite material, 1-5g of dispersant, 1-10g of defoamer, 20-40g of water; The proportions of the raw materials in component B are as follows: 200-300 g of water, 20-40 mL of anhydrous ethanol, 1-5 mL of glacial acetic acid, and 1-5 mL of ethyl orthosilicate; The proportions of the raw materials in the component C are as follows: 200-400 g of oligomer emulsion, 60-80 g of thickener, and 1-10 g of crosslinking agent.

[0018] Optionally, the dispersant is selected from at least one of polyethylene glycol trimethoxysilyl propyl ether, polydimethylsiloxane, epoxy silane, and amino silane; The defoaming agent is selected from one or a combination of two or more of hexamethylenetetramine, urea, ammonia water and ammonium carbonate; The oligomer emulsion is selected from one or two combinations of 3-aminopropyltriethoxysilane, modified polyvinyl alcohol, and silicone-modified polyurethane; The thickener is selected from one or a combination of lauramidopropyl betaine, sodium carboxymethyl cellulose and sodium polyacrylate; The crosslinking agent is selected from one or a combination of 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide.

[0019] Optionally, the regulating viscosity and pH value includes: adjusting the viscosity to 800-1000 mPa·s and the pH value to 7-8.

[0020] Compared with the prior art, the present invention has the following beneficial effects: The present invention prepares a spherical TiO 2 The inorganic particle composite material is coated by first preparing rutile TiO 2 The prepared rutile TiO 2 The balls are sprayed onto the surface of the inorganic particle core material through a fluidized bed to form spherical TiO 2 Coated inorganic particle composite material. Among them, TiO 2 The coated inorganic particle composite material is a spherical structure, which can increase the TiO 2 The specific surface area of ​​TiO 2 Spherical particles are coated onto the surface of inorganic particle core materials such as SiO 2 、Al 2 O 3, spinel, etc. When multiple spheres gather into a large sphere, the surface of the new sphere is smoother, the directionality of light reflection is stronger, tending to mirror reflection, making the reflected light more concentrated. 2 The inorganic particles have different refractive index and light scattering properties. When they are combined together, they can form a multi-level scattering structure, increase the scattering path of light inside the material, and thus significantly enhance its reflection effect within a specific wavelength range. 2 The spectral response range of the composite material may be narrow, while the composite material can broaden its response range to light through the synergistic effect of different components, including ultraviolet light, visible light and even near-infrared light, thereby improving the overall reflection performance. In addition, the composite material prepared by the present invention is coated with spherical TiO 2 Coated on inorganic particles, improving the spherical TiO 2 Stability in harsh environments, such as acid and alkali corrosion, thus maintaining its long-term reflective effect; In addition to the reflective effect, spherical TiO 2 Composite materials may also have other additional functions, such as photocatalytic properties, thermal insulation properties, etc. The enhancement of these functionalities can further expand their application areas.

[0021] The present invention adopts spherical TiO 2 The solar infrared light reflective coating was prepared by coating the inorganic particle composite material and it was confirmed that the solar light reflectance of the coating was above 80%, and the infrared light reflectance was above 80%, showing good light reflective performance.

[0022] The present invention uses titanium tetraisopropoxide, anhydrous ethanol and glacial acetic acid as reactants, and obtains rutile TiO by controlling reaction conditions, purification steps and calcination conditions. 2 The obtained rutile TiO 2 The ball has high purity and appropriate particle size, which is conducive to improving the coating effect. In the subsequent fluidized bed spraying process, the appropriate particle size helps to improve the uniformity and density of the coating. If the particle size is too small, it may cause powder agglomeration and affect the coating effect. The TiO prepared by the present invention under the above raw material composition and production conditions 2 The balls are more suitable, which is beneficial to improve the coating effect and make the effect of the prepared coating more significant. In addition, the high-purity TiO 2 The balls can reduce the impact of impurities on the coating process and final product performance.

[0023] The present invention adopts fluidized bed technology to prepare rutile TiO 2 The balls are sprayed onto the surface of inorganic particles to form spherical TiO 2 Spherical TiO 2 Coated inorganic particle composite material. 1) The present invention comprises TiO2 The addition of ethanol to the TiO 2 The particles are dispersed in the form of a colloid, and the solution is adjusted to a suitable viscosity with the aid of at least one of polyacrylate, polyacrylic amine and polyvinyl alcohol, thereby improving the coating effect. 2) The present invention uses air as the fluidizing gas, adjusts the height of the fluidized bed to 20-60cm, and the bed pressure to 4.5~5.5MPa, which can not only avoid chemical reactions with the reactants, but also enable the inorganic particle core material to be in a good fluidized state, thereby ensuring the uniformity of the coating. 3) The present invention sets the air flow velocity to 0.1-0.5m / s. The fluidization velocity is one of the key parameters for the operation of the fluidized bed. If the fluidization velocity is too low, the particles cannot be fully fluidized, resulting in uneven coating; and if the fluidization velocity is too high, the particles may be carried out of the fluidized bed by the gas, resulting in material loss and environmental pollution, and will also affect the coating effect. The fluidization velocity of the present invention is an optimal fluidization velocity range determined by repeated experiments. 4) Temperature also has an important influence on the coating process, including spherical TiO 2 The chemical reaction rate and coating adhesion, etc. If the temperature is too low, the spherical TiO 2 It cannot fully react with the surface of the inorganic particle core material, resulting in a weak coating; too high a temperature may cause TiO 2 Therefore, the present invention is based on TiO 2 According to the characteristics of the inorganic particle core material, the inlet temperature of the fluidized bed is precisely controlled to be 30-80°C and the outlet temperature is 80-120°C. 2 The spherical solution is sprayed onto the surface of the fluidized inorganic particle core material through a spray gun. Different from the vapor deposition method, not only the operating conditions are milder, but also the spherical TiO 2 The inorganic particle-coated composite material is conducive to the formation of a coating with better light reflectivity and multifunctionality. The addition of inorganic particles can make up for the single use of TiO 2 The objective shortcomings of the coating are improved by spherical TiO 2 It is compounded with inorganic particles to form a coating with special structure and properties, which not only retains the spherical TiO 2 In addition to the light reflection and other properties, the inorganic particles can also be used for reinforcement, toughening, heat insulation and other functions to achieve complementary and improved performance.

[0024] The spherical TiO 2 The coated inorganic particle composite material is used to prepare the coating, including: ① spherical TiO 2 The coated inorganic particle composite material is mixed with a dispersant, a defoamer and water, and sand-milled to obtain component A. The selected dispersant produces silanol groups after hydrolysis. The groups carried have the characteristics of a polymer dispersant and can react with spherical TiO 2Good cross-linking, after sand grinding, can obtain a mixed dispersion with stable performance, low number and high solid content, ensuring spherical TiO 2 The coated inorganic particle composite material is evenly dispersed in the system, providing good basic performance for the coating. ② Mix and react water, anhydrous ethanol, glacial acetic acid and ethyl orthosilicate to obtain component B, in which ethyl orthosilicate slowly hydrolyzes to form a stable semi-hydrolyzate. In this state, the material is not prone to large-scale polymerization and precipitation, providing good film-forming properties for the coating, allowing the coating to form a uniform film on the surface of the substrate, ensuring the integrity and stability of the coating. ③ The oligomer emulsion, thickener and crosslinker are mixed and reacted to obtain component C. The selected oligomer emulsion has a certain degree of polymerization and rich silanol groups. The solvent is water and the solid content is 25-35%wt. The selected thickener can reduce the surface tension of water and make the material easier to be wetted. The synergistic effect of the two can improve the hydrophilicity of the coating. The improvement of hydrophilicity makes the coating easier to contact with water during use. For example, in the self-cleaning process, water can spread more quickly and fully on the surface of the coating to take away dirt. The crosslinker causes the oligomer emulsion to undergo a dehydration condensation reaction with the thickener, and the thickener with extremely high hydrophilicity is fixed in the coating. Even in long-term use or complex environments, the hydrophilicity, antibacterial and antistatic properties of the coating can be maintained. As a result, the product of the hydrolysis of ethyl orthosilicate in component B can undergo a crosslinking polymerization reaction with the components in component A and the groups in component C, further enhancing the structural strength and stability of the coating. For example, in the curing process of the coating, the crosslinking reaction causes the coating to form a three-dimensional network structure, improving the hardness, wear resistance and corrosion resistance of the coating. In summary, component A, component B and component C each play an important role in the coating system, and through cross-linking reaction, synergistic dispersion and other modes of action, they achieve synergistic enhancement of coating performance, so that the coating has excellent self-cleaning function, reflective performance, hydrophilicity, stability and durability.

[0025] The light-reflective coating prepared by the present invention has a wide range of application prospects, and the following are its specific applications: In the field of construction, it is mainly used as exterior wall coating. Its high reflectivity can reduce the building's absorption of solar radiation heat and lower the indoor temperature. At the same time, the addition of inorganic particles enhances the coating's wear resistance and corrosion resistance, extending the service life of the exterior wall. It can also be used as roof coating. Its good waterproof performance can effectively prevent rainwater penetration and protect the roof structure.

[0026] In the field of transportation, it is mainly used as road marking paint, and its reflective properties help improve the visibility of road markings at night or in low visibility conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0028] Figure 1 : TiO prepared by the present invention 2 Schematic diagram of the ball; Figure 2 : The spherical TiO prepared by the present invention 2 Coated SiO 2 Schematic diagram of composite material particles; Figure 3 : The spherical TiO prepared by the present invention 2 Al coating 2 O 3 Schematic diagram of composite material particles; Figure 4 : The spherical TiO prepared by the present invention 2 Schematic diagram of coated spinel composite particles; Figure 5 :The spherical TiO 2 Flow chart of coating inorganic particle composite materials; Figure 6 :Spherical TiO 2 Al coating 2 O 3 Composite materials (TiO 2 / Al 2 O 3 ) and the spectral reflectance curve of commercially available P25 powder. DETAILED DESCRIPTION

[0029] In order to better understand the present invention, the content of the present invention is further clearly set forth in conjunction with the embodiments below, but the protection content of the present invention is not limited to the following embodiments. In the following description, a large number of specific details are provided in order to provide a more thorough understanding of the present invention. However, it is obvious to those skilled in the art that the present invention can be implemented without one or more of these details.

[0030] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.

[0031] Unless otherwise specified, all raw materials are from commercially available products and do not contain other unspecified components except inevitable impurities unless otherwise specified.

[0032] The following examples 1-3 are for preparing TiO 2 Specific implementation plan of the ball.

[0033] Example 1: 0.165 g of titanium tetraisopropoxide was added to 80 mL of anhydrous ethanol and 8 mL of glacial acetic acid and stirred for 10 min. The solution was poured into a 150 mL polyethylene reactor and reacted at 180 ° C for 3 h. After the reaction, the precipitate was centrifuged at 8000 rpm for 3 min, washed twice with distilled water and anhydrous ethanol respectively, dried in an oven at 70 ° C for 12 h after the ultrasonic treatment, and calcined at 900 ° C for 4 h to obtain TiO 2 ball.

[0034] Example 2: 0.330 g of titanium tetraisopropoxide was added to 80 mL of anhydrous ethanol and 8 mL of glacial acetic acid and stirred for 10 min. The solution was poured into a 150 mL polyethylene reactor and reacted at 150 ° C for 4 h. After the reaction, the precipitate was centrifuged at 8000 rpm for 3 min, washed twice with distilled water and anhydrous ethanol respectively, dried in an oven at 65 ° C for 20 h after the ultrasonic treatment, and calcined at 920 ° C for 3 h to obtain TiO 2 ball.

[0035] Example 3: 0.495 g of titanium tetraisopropoxide was added to 80 mL of anhydrous ethanol and 8 mL of glacial acetic acid and stirred for 10 min. The solution was poured into a 150 mL polyethylene reactor and reacted at 200 ° C for 2 h. After the reaction, the precipitate was centrifuged at 8000 rpm for 3 min, washed twice with distilled water and anhydrous ethanol respectively, dried in an oven at 75 ° C for 15 h after the ultrasonic treatment, and calcined at 950 ° C for 2 h to obtain TiO 2 ball.

[0036] TiO prepared in the embodiment of the present invention 2 The surface morphology of the ball was characterized by Hitachi SU8100, as shown in Figure 1 As shown, TiO 2 The spheres are regular spherical in shape, with a diameter greater than 1000nm.

[0037] The following examples 4-6 are for preparing spherical TiO 2 Specific embodiments of coated inorganic particle composite materials.

[0038] See also Figure 5 The present invention prepares spherical TiO 2 The steps of coating the inorganic particle composite material include: feeding, feeding completion, flowing, circulating flow, spraying and loading completion. The detailed implementation scheme is shown in Examples 4-6.

[0039] Example 4: Select SiO with a particle size of 200 nm 2The particles were washed and dried with distilled water and anhydrous ethanol for later use; the feed valve of the fluidized bed was opened, and the dried inorganic particle core material was introduced into the silo of the fluidized bed; the feed valve was closed, and the height of the fluidized bed was adjusted to 20 cm, and the bottom gas pump was started, and the air flow velocity was adjusted to 0.1 m / s, so that the bed particles entered a fluidized state; the TiO prepared in Example 1 was added 2 Add ethanol to prepare 60% TiO 2 The viscosity of the ethanol solution was measured using a viscometer, and the viscosity was adjusted to 800 mPa·s using polyacrylate before being passed into the liquid flow chamber; the spray pressure was set to 0.5 MPa and the spray rate was 60 L / h; when spraying TiO 2 When spraying the solution, keep the inlet temperature at 60°C and the outlet temperature at 105°C to promote the evaporation and solidification of the solution. When the predetermined thickness is reached, stop spraying TiO 2 Ethanol solution; after stopping spraying, continue to maintain the airflow to ensure complete drying of the particles; after the coating is completed, the spherical TiO 2 Coated SiO 2 Composite material particles are discharged.

[0040] The spherical TiO prepared in this example 2 Coated SiO 2 The surface morphology of the composite material was characterized by a German ZEISS GeminiSEM 300. Figure 2 As shown, spherical TiO 2 Coated SiO 2 The composite material particles are regular spherical and micrometer-sized.

[0041] Example 5: Select Al with a particle size of 400 μm 2 O 3 The particles were washed and dried with distilled water and anhydrous ethanol for later use; the feed valve of the fluidized bed was opened, and the dried inorganic particle core material was introduced into the silo of the fluidized bed; the feed valve was closed, and the height of the fluidized bed was adjusted to 40 cm, and the bottom gas pump was started, and the air flow velocity was adjusted to 0.3 m / s, so that the bed particles entered a fluidized state; the TiO prepared in Example 2 was added 2 Add ethanol to make 60% TiO 2 The viscosity of the ethanol solution was measured using a viscometer, and the viscosity was adjusted to 905 mPa·s using polyacrylamide before being passed into the liquid flow chamber; the spray pressure was set to 0.3 Mpa and the spray rate was 100 L / h; when spraying TiO 2 When spraying the solution, keep the inlet temperature at 80℃ and the outlet temperature at 120℃ to promote the evaporation and solidification of the solution. When the predetermined thickness is reached, stop spraying TiO 2Ethanol solution; after stopping spraying, continue to maintain the airflow to ensure complete drying of the particles; after the coating is completed, the spherical TiO 2 Al coating 2 O 3 Composite material particles are discharged.

[0042] The spherical TiO prepared in this example 2 Al coating 2 O 3 The surface morphology of the composite material was characterized by a German ZEISS GeminiSEM 300. Figure 3 As shown, spherical TiO 2 Al coating 2 O 3 The composite material is in regular spherical shape and has a size of micrometer level.

[0043] Example 6: Select spinel particles with a particle size of 600 nm, use distilled water and anhydrous ethanol to wash and dry them for use; open the feed valve of the fluidized bed, and pass the dried inorganic particle core material into the silo of the fluidized bed; close the feed valve, adjust the height of the fluidized bed to 60 cm, start the bottom gas pump, adjust the air flow speed to 0.1 m / s, and make the bed particles enter the fluidized state; add the TiO prepared in Example 3 2 Add ethanol to make 60% TiO 2 The viscosity of the ethanol solution was measured using a viscometer, and the viscosity was adjusted to 1000 mPa·s using polyvinyl alcohol before being passed into the liquid flow chamber; the spray pressure was set to 0.2 MPa and the spray rate was 10 L / h; when spraying TiO 2 When spraying the solution, keep the inlet temperature at 30°C and the outlet temperature at 80°C to promote the evaporation and solidification of the solution. When the predetermined thickness is reached, stop spraying TiO 2 Ethanol solution; after stopping spraying, continue to maintain the airflow to ensure complete drying of the particles; after the coating is completed, the spherical TiO 2 The coated spinel composite material particles are discharged.

[0044] The spherical TiO prepared in this example 2 The surface morphology of the coated spinel composite material was characterized by a German ZEISS GeminiSEM 300. Figure 4 As shown, spherical TiO 2 The coated spinel composite material is in a regular spherical shape and has a size of micrometer level.

[0045] The following Examples 7-10 are specific implementation plans for preparing coatings.

[0046] Example 7: Take 30g of water, 3g of polyethylene glycol trimethoxysilyl propyl ether and 5g of hexamethylenetetramine, mix them evenly under stirring, and add the spherical TiO prepared in Example 4. 2 Coated SiO 2 10 g of the composite material was fully dispersed and then sand-milled to obtain a uniform component A; Take 250g of water, 25mL of anhydrous ethanol and 3mL of glacial acetic acid respectively, mix them evenly, slowly add 2.7mL of ethyl orthosilicate under stirring, and slowly hydrolyze to obtain component B with cross-linking function; Take 300g of 3-aminopropyltriethoxysilane, add 70g of laurylamidopropyl betaine, 1.5g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide and 1.5g of N-hydroxysuccinimide under stirring, and react at 60°C for 2h to obtain component C; The prepared component A, component B and component C are fully stirred and mixed in a volume ratio of 6:3:1, and the viscosity of the mixture is adjusted to 800 mPa·s and the pH value is adjusted to 7.0. After mixing evenly, a finished reflective coating product can be obtained.

[0047] Example 8: Take 20g water, 1g polydimethylsiloxane and 1g urea, mix them evenly under stirring, and add the spherical TiO prepared in Example 5. 2 Al coating 2 O 3 12 g of the composite material was fully dispersed and then sand-milled to obtain a uniform component A; Take 200g of water, 20mL of anhydrous ethanol and 1mL of glacial acetic acid, mix them evenly, and slowly add 1mL of ethyl orthosilicate under stirring to perform a slow hydrolysis reaction to obtain component B with a cross-linking function; Take 100g of 3-aminopropyltriethoxysilane and 100g of silicone-modified polyvinyl alcohol, add 40g of laurylamidopropyl betaine, 20g of sodium polyacrylate and 1g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide under stirring, and react at 60°C for 2h to obtain component C; The prepared component A, component B and component C are fully stirred and mixed in a volume ratio of 6:3:1, and the viscosity of the mixture is adjusted to 900 mPa·s and the pH value is adjusted to 7.8. After mixing evenly, a finished reflective coating product can be obtained.

[0048] Example 9: Take 40g of water, 5g of epoxysilane and 10g of ammonia water, mix them evenly under stirring, and add the spherical TiO prepared in Example 6. 2 20 g of the coated spinel composite material was fully dispersed and then sand-milled to obtain a uniform component A; Take 300g of water, 40mL of anhydrous ethanol, and 5mL of glacial acetic acid and mix them evenly. Slowly add 5mL of ethyl orthosilicate under stirring to perform a slow hydrolysis reaction to obtain component B with a cross-linking function. Take 400g of silicone-modified polyurethane emulsion, add 80g of sodium carboxymethyl cellulose and 10g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide under stirring, and react at 60°C for 2h to obtain component C; The prepared component A, component B and component C are fully stirred and mixed in a volume ratio of 6:3:1, and the viscosity of the mixture is adjusted to 1000 mPa·s and the pH value is adjusted to 8.5. After mixing evenly, a finished reflective coating product can be obtained.

[0049] Example 10: Take 35g of water, 4g of aminosilane and 8g of ammonium carbonate, mix them evenly under stirring, and add the spherical TiO prepared in Example 4. 2 Coated SiO 2 18 g of the composite material was fully dispersed and then sand-milled to obtain a uniform component A; Take 280g of water, 35mL of anhydrous ethanol and 4mL of glacial acetic acid respectively, mix them evenly, slowly add 4mL of ethyl orthosilicate under stirring, and slowly hydrolyze to obtain component B with cross-linking function; Take 270g of 3-aminopropyltriethoxysilane, add 75g of sodium polyacrylate and 7g of N-hydroxysuccinimide under stirring, and react at 60°C for 2h to obtain component C; The prepared component A, component B and component C are fully stirred and mixed in a volume ratio of 6:3:1, and the viscosity of the mixture is adjusted to 950 mPa·s and the pH value is adjusted to 8.0. After mixing evenly, a finished reflective coating product can be obtained.

[0050] The following Comparative Examples 1-8 are comparative implementation plans.

[0051] Comparative Example 1: This comparative example is different from Example 7 in that: spherical TiO 2 Coated SiO 2 The composite material was replaced with TiO prepared in Example 1. 2 ball.

[0052] Comparative Example 2: This comparative example is different from Example 7 in that: spherical TiO 2 Coated SiO 2 The composite material was replaced with commercially available P25 powder (titanium dioxide).

[0053] Comparative Example 3: This comparative example is different from Example 7 in that: spherical TiO 2 Coated SiO 2The composite material was replaced with SiO with a particle size of 200 nm. 2 Particles.

[0054] Comparative Example 4: This comparative example is different from Example 8 in that: spherical TiO 2 Coated SiO 2 The composite material was replaced with Al with a particle size of 400 nm. 2 O 3 Particles.

[0055] Comparative Example 5: This comparative example is different from Example 9 in that: spherical TiO 2 Coated SiO 2 The composite material was replaced with spinel particles with a particle size of 600 nm.

[0056] Comparative Example 6: This comparative example is different from Example 4 in that SiO 2 -TiO 2 Composite particles, refer to Example 1 in CN112972275A, specifically: 0.4g polyvinyl pyrrolidone (PVP) was dissolved in anhydrous ethanol, 0.3g TiO 2 The spheres were dispersed in an ultrasonic cell disruptor for 20 min, and 30 mL of anhydrous ethanol solution of tetraethyl orthosilicate (TEOS) was added dropwise under 350 r / min electric stirring, and ammonia water was added to control the pH to 9.0. The TEOS was added dropwise in 2.5 h, and reacted in a 35°C constant temperature water bath for 4 h. After the reaction was completed, the reaction solution was cooled, centrifuged, washed with deionized water several times, and dried in a 45°C vacuum drying oven to obtain SiO 2 -TiO 2 Composite particles.

[0057] Comparative Example 7: This comparative example is different from Example 5 in that the bed pressure is set to 3 MPa, the air flow velocity is set to 0.8 m / s, the inlet temperature is set to 120°C, and the outlet temperature is set to 150°C.

[0058] Comparative Example 8: This comparative example is different from Example 6 in that the bed pressure is set to 4 MPa, the air flow velocity is 1.0 m / s, the inlet temperature is 100°C, and the outlet temperature is 60°C.

[0059] Next, the contents of the evaluation test will be described.

[0060] 1. If Figure 6 The curve is shown in Figure 1, which was measured by UV-visible diffuse reflectance spectroscopy (UV-vis DRS) using a Shimdzu UV-3600 spectrophotometer equipped with an integrating sphere. Figure 6 It can be seen that compared with the full-band spectral reflectance of P25, the spherical TiO prepared by the present invention2 / Al 2 O 3 The reflectivity curve of the composite material is significantly higher than that of P25. In the ultraviolet band of 10~400nm, the spherical TiO 2 / Al 2 O 3 The reflectivity of the composite material is slightly higher than that of P25; in the visible light band of 400~700nm, the spherical TiO 2 / Al 2 O 3 The reflectivity of the composite material is greatly increased; in the near-infrared band of 700~2500nm, the spherical TiO 2 / Al 2 O 3 The overall reflectivity of the composite material is higher than that of P25. This shows that the spherical TiO 2 / Al 2 O 3 The composite material can improve the reflectivity of the material in the 400-2500nm band.

[0061] 2. The coatings prepared in Examples 7-10 and Comparative Examples 1-8 were used to perform reflectance test.

[0062] The spectral reflectance characteristics of the samples in the visible and ultraviolet spectral ranges were tested using a UV-Vis spectrophotometer, and the reflectance spectral characteristics of the samples in the infrared spectral range were tested using an FT-IR spectrometer.

[0063] (1) Solar reflectance: Solar reflectance ( ) is usually used to measure an object's ability to reflect sunlight, and its calculation formula is: , Where: ρ represents the sunlight reflectance, unit is g; ρλ i Indicates wavelength as λ i Spectral reflectance, Es(λ i ) indicates the wavelength λ i The spectral intensity of solar radiation at a location, usually expressed in W / m²·μm, Δλ i Indicates the wavelength interval, usually taken as λ i+1 With λ i-1 Half of the wavelength difference, unit is nm, Σ represents the summation, and the range covers the main wavelength region of solar radiation, such as 250nm to 2500nm.

[0064] (2) Near infrared reflectance: Near infrared reflectance (NIR) refers to the ability to reflect light under near infrared light (780-2500nm). The calculation formula is: , Where: NIR represents near-infrared reflectivity, Rsample represents the reflectance value of the sample, that is, the reflected light intensity of the sample in the near-infrared light band, Rdark represents the dark background value, that is, the measurement value when there is no light irradiation, which is used to eliminate the influence of ambient light on the measurement results, and Rwhite represents the white standard value, that is, the value of completely reflected light, which is used as a reference standard.

[0065] The results of the above performance tests are shown in the following table: From the above data, it can be seen that the spherical TiO 2 Compared with Comparative Examples 1-8, the light reflective coating coated with the inorganic particle composite material has higher solar reflectance and near-infrared reflectance, indicating that the coating prepared by the present invention has a more significant reflective effect in the near-infrared region.

[0066] 3. Determine the corrosion resistance and self-cleaning properties of the coatings prepared in Examples 7-10 and Comparative Examples 1-8.

[0067] The prepared coatings were sprayed on stainless steel plates (150 mm × 100 mm × 1 mm) with a thickness of 50 ± 3 μm, cured, and dried as test specimens.

[0068] (1) Corrosion resistance: Tested according to the method specified in GB / T1771-2007 "Determination of neutral salt spray resistance of paints and varnishes". Test conditions: NaCL solution concentration (50±5) g / l, pH value of collected solution 7.0, temperature in salt spray chamber 35±2℃, 80cm 2 The salt spray solution collection rate is 2.0 mL / h, and the test duration is 96 hours. At the end of the test, observe whether there is blistering, rusting, cracking, and peeling.

[0069] (2) Self-cleaning property: The contact angle of the sample surface to water is measured using a contact angle meter. The test method is the drop method, that is, a drop of liquid is dropped onto a glass slide through a syringe needle, and the contact angle is read using the tangent method; measure at least 3 locations and take the average value. Contaminate the sample surface with oil, measure the contact angle of the sample surface to water, and then place it under ultraviolet light for 12 hours, and then measure the contact angle of the sample surface to water again. The unit of the contact angle is: ° (degree).

[0070] The above test results are shown in the following table: The above test results show that the coating prepared by the present invention has good corrosion resistance. In the 96h neutral salt spray corrosion test, no blistering, rusting, cracking and peeling occurred. The initial static contact angle of the sample of the present invention is greater than 150°, and the contact angle decreases significantly after being contaminated by oil. After being irradiated by ultraviolet light for 12h, the static contact angle of the sample surface recovers and rises to greater than 120°, and has good self-cleaning ability.

[0071] In summary, the light-reflective coating prepared by the present invention not only has high light-reflective performance, but also has corrosion resistance and self-cleaning effects, and can be better applied to exterior wall or traffic marking coatings.

[0072] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Other modifications or equivalent substitutions made to the technical solution of the present invention by ordinary technicians in the field should be included in the scope of the claims of the present invention as long as they do not depart from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for preparing a spherical TiO2-coated inorganic particle composite material, characterized in that: The following steps are involved: S01: Preparation of rutile TiO2 balls: Add titanium tetraisopropoxide to anhydrous ethanol and glacial acetic acid, stir, and perform hydrothermal reaction in a reactor. After the reaction, centrifuge the precipitate, wash it twice with distilled water and anhydrous ethanol respectively, and after the ultrasonic treatment, dry and calcine to obtain rutile TiO2 balls; S02: Preparation of spherical TiO2-coated inorganic particle composite materials: open the feed valve of the fluidized bed, and pass the inorganic particle core material into the silo of the fluidized bed; close the feed valve, adjust the height of the fluidized bed, start the bottom gas pump, and adjust to the set air flow speed to make the bed particles enter a fluidized state; add the TiO2 balls to ethanol to obtain a TiO2 ethanol solution, and after adjusting the viscosity, pass it into a liquid flow bin, set the spray pressure and spray rate, spray the TiO2 ethanol solution onto the surface of the inorganic particle core material, maintain appropriate air inlet temperature and air outlet temperature, and stop spraying the TiO2 ethanol solution after reaching a predetermined thickness, and continue to maintain the air flow to completely dry the particles to obtain a spherical TiO2-coated inorganic particle composite material.

2. The method for preparing a spherical TiO2-coated inorganic particle composite material according to claim 1, characterized in that: In the step S01, the weight of titanium tetraisopropoxide is 0.165-0.495 g, the volume of anhydrous ethanol is 50-100 mL, and the volume of glacial acetic acid is 5-10 mL.

3. The method for preparing a spherical TiO2-coated inorganic particle composite material according to claim 2, characterized in that: The temperature of the hydrothermal reaction in step S01 is 150°C-200°C, and the reaction time is 2-4h. The drying temperature is 60-80°C and the drying time is 12-24 hours. The calcination temperature is 900-950° C. and the calcination time is 2-4 hours.

4. The method for preparing a spherical TiO2-coated inorganic particle composite material according to claim 3, characterized in that: In the step S02, the inorganic particle core material is at least one of silicon dioxide, aluminum oxide, and spinel, and the particle size is 100-700 nm.

5. The method for preparing a spherical TiO2-coated inorganic particle composite material according to claim 4, characterized in that: In step S02, the height of the fluidized bed is 20-60 cm, the bed pressure is 4.5-5.5 MPa, and the air flow velocity is 0.1-0.5 m / s.

6. The method for preparing a spherical TiO2-coated inorganic particle composite material according to claim 5, characterized in that: The mass concentration of TiO2 balls in the TiO2 ethanol solution in step S02 is 60%, and the viscosity of the TiO2 ethanol solution is regulated by the following raw materials, including at least one of polyacrylate, polyacrylic amine and polyvinyl alcohol.

7. The method for preparing a spherical TiO2-coated inorganic particle composite material according to claim 6, characterized in that: In the step S02, the viscosity of the TiO2 ethanol solution is adjusted to 800-1000 mPa·s, the spray pressure is 0.2-0.5 MPa, the spray rate is 10-100 L / h; the air inlet temperature is 30-80°C, the air outlet temperature is 80-120°C; and the spraying time is controlled at 30-40 min.

8. Use of the spherical TiO2 coated inorganic particle composite material obtained by the preparation method of the spherical TiO2 coated inorganic particle composite material according to any one of claims 1 to 7 in light reflective coatings.

9. The light-reflecting coating according to claim 8, characterized in that: The coating is obtained by the following preparation method: providing an oligomer emulsion, a thickener, a crosslinking agent, a dispersant, a defoaming agent, tetraethyl orthosilicate, glacial acetic acid, anhydrous ethanol and water; mixing the spherical TiO2-coated inorganic particle composite material with water, a dispersant and a defoaming agent to obtain component A; mixing and reacting water, anhydrous ethanol, glacial acetic acid and tetraethyl orthosilicate to obtain component B; mixing and reacting the oligomer emulsion, a thickener and a crosslinking agent to obtain component C; mixing component A, component B and component C in a volume ratio of 6:3:1, adjusting the viscosity and pH value to obtain a coating; The proportions of the raw materials in the component A are as follows: 10-20 g of spherical TiO2-coated inorganic particle composite material, 1-5 g of dispersant, 1-10 g of defoamer, and 20-40 g of water; The proportions of the raw materials in component B are as follows: 200-300 g of water, 20-40 mL of anhydrous ethanol, 1-5 mL of glacial acetic acid, and 1-5 mL of ethyl orthosilicate; The proportions of the raw materials in the component C are as follows: 200-400 g of oligomer emulsion, 60-80 g of thickener, and 1-10 g of crosslinking agent; The dispersant is selected from at least one of polyethylene glycol trimethoxysilyl propyl ether, polydimethylsiloxane, epoxy silane and amino silane; The defoaming agent is selected from one or a combination of two or more of hexamethylenetetramine, urea, ammonia water and ammonium carbonate; The oligomer emulsion is selected from one or two combinations of 3-aminopropyltriethoxysilane, modified polyvinyl alcohol, and silicone-modified polyurethane; The thickener is selected from one or a combination of lauramidopropyl betaine, sodium carboxymethyl cellulose and sodium polyacrylate; The crosslinking agent is selected from one or a combination of 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide.

10. The light-reflecting coating according to claim 9, characterized in that: The regulating viscosity and pH value comprises: regulating the viscosity to 800-1000 mPa·s and the pH value to 7-8.

Citation Information

Patent Citations

  • Preparation method for synthesizing sheet-type cladding material by fluidized bed gas-phase method

    CN103773084A

  • Titanium dioxide / hollow micro-bead composite particles, solar light reflection heat-insulating filler, coating and preparation method of titanium dioxide / hollow micro-bead composite particles

    CN104046117A

  • Water-based two-component polyurethane, light reflective heat-insulation and heat-preservation colored sand and preparation method thereof

    CN114315198A

  • Method for coating solid-state battery positive electrode material, positive electrode material, and solid-state battery

    WO2022121636A1